English translation and validation of the Afterlife Belief Scale for British Muslims - Ghayas, Saba; Strait, John B.; Malik, Misbah (European Scientific Journal, ESJ, 2025)
The purpose of the current study was to translate and validate the Afterlife Belief scale into the English language. To translate the scale, the forward-backward method was used. Through the committee approach, the English version of the scale was finalized. The English version of the Afterlife Belief Scale was administered to a sample of 300 British Muslims, with a mean age of 34.5 and a standard deviation of 3.5. Confirmatory factor analysis was conducted, and the results revealed excellent model fit indices with a two-factor structure. The original scale had a three-factor structure; however, in the current study, all items related to extinction-based afterlife Belief were found to have low loadings, so analysis was carried out on the remaining items. Keeping in view the results and feedback from participants and experts, the two-factor structure was finalized with excellent model fit indices (CFI, GFI, TLI, RMSEA, RMR). Alpha reliability indices of both subscales were excellent. Furthermore, in order to find the convergent and divergent validity evidence, the English version of the Afterlife Belief Scale, the Short Muslim Practice and Belief Scale, the Arabic Death Anxiety Scale, and the Penn Inventory of Scrupulosity Scale were administered to the 150 British Muslims. Correlation analysis provided evidence of convergent validity as afterlife beliefs were found to be correlated with death anxiety, scrupulosity, and religiosity. The findings support the English version of the Afterlife Belief Scale as a psychometrically sound instrument for assessing afterlife beliefs among British Muslims.